Dogs in the News. - Lewis, Martyn, 1945- (Little Brown and Company, 1992)
By the author of "Cats in the News", this is a similar collection of doggie stories. The book is a light-hearted celebration of dogs of every sort - the lovable and the ludicrous, the timid and the terrible, the heroic and the ridiculous, the bizarre and the unbelievable.